The Role of the Prosecutor's Office in Enforcing Anti-Corruption Laws within Local Governments: A Socio-Legal Perspective - Purnomo, Cahyo; Fuad, Fokky; Suartini, Suartini (Jurnal Hukum Magnum Opus, 2025)
This study aims to analyze the role of the Prosecutor’s Office in enforcing anti-corruption laws within local governments from a socio-legal perspective. The research adopts a normative juridical method using a statutory and conceptual approach. Corruption is classified as an extraordinary crime that must be eradicated within society. In Indonesia, corruption cases are predominantly committed by local government officials. The enforcement of anti-corruption laws in Indonesia is primarily dominated by the Prosecutor’s Office. In this context, a socio-legal perspective is required to support the enforcement of anti-corruption laws. Law enforcement actions against corruption at the local government level constitute social actions that inherently involve socio-legal aspects, as they produce both positive and counterproductive social impacts. The role of the Prosecutor’s Office in enforcing anti-corruption laws within local governments must account for these social impacts. The findings of this study reveal that law enforcement against corruption generates diverse social outcomes. The positive impacts include increased support from the public, NGOs, and local governments for the law enforcement process. Such support typically arises when law enforcement actions are carried out transparently and in accordance with procedural norms. Conversely, counterproductive impacts include disruptions to local development programs, particularly when human resources in local governments become preoccupied or hindered by legal proceedings. Government officials often hesitate to assume strategic financial positions due to fear of legal repercussions, leading to stagnation in the execution of critical tasks, especially those involving state financial management.